2016
DOI: 10.3390/jcm5070061
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Acylated Ghrelin and Obestatin Levels in Childhood Obesity and Their Association with Insulin Resistance, Metabolic Syndrome, and Oxidative Stress

Abstract: Background: Ghrelin is a 28-amino acid peptide with an orexigenic property, which is predominantly produced by the stomach. Acylated ghrelin is the active form of this hormone. Obestatin is a 23-amino acid peptide which is produced by post-translational modification of a protein precursor that also produces ghrelin. Obestatin has the opposite effect of ghrelin on food intake. The aim of this study was to evaluate acylated ghrelin and obestatin levels and their ratio in obese and normal-weight children and adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
33
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 65 publications
(78 reference statements)
7
33
1
3
Order By: Relevance
“…Total ghrelin/obestatin ratio has been demonstrated to correlate negatively with body mass index, waist circumference, waist/hip ratio and insulin ( 16 ). More recently, AG/obestatin ratio was shown to be significantly lower in children and adolescents with obesity compared to their normal-weight counterparts ( 35 ). In addition, the total ghrelin/obestatin ratio was also reduced in hypertensive individuals compared with normotensive control ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Total ghrelin/obestatin ratio has been demonstrated to correlate negatively with body mass index, waist circumference, waist/hip ratio and insulin ( 16 ). More recently, AG/obestatin ratio was shown to be significantly lower in children and adolescents with obesity compared to their normal-weight counterparts ( 35 ). In addition, the total ghrelin/obestatin ratio was also reduced in hypertensive individuals compared with normotensive control ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ghrelin also has direct metabolic effects in the periphery, such as endopancreatic function and altered glucose metabolism . Intravenous ghrelin administration in humans has been demonstrated to promote a favorable effect on glucose metabolism, insulin sensitivity, and lipolysis inhibition . Decreased ghrelin levels in patients with type 2 diabetes mellitus are associated with an increase in abdominal adiposity and insulin resistance .…”
Section: Discussionmentioning
confidence: 99%
“…30 Intravenous ghrelin administration in humans has been demonstrated to promote a favorable effect on glucose metabolism, insulin sensitivity, and lipolysis inhibition. [30][31][32] Decreased ghrelin levels in patients with type 2 diabetes mellitus are associated with an increase in abdominal adiposity and insulin resistance. [30][31][32] Overall, ghrelin as an AGR-conscious therapeutic strategy might also be associated with a significant reduction in cardiovascular events.…”
Section: Ghrelin and Heart Failurementioning
confidence: 99%
“…Besides, the current data showed serum concentration of obestatin was decreased in obese children and were negatively associated with C5a. Taskin et al's study showed that serum obestatin levels were significantly lower in an obese polycystic ovary syndrome group, while Razzaghy‐Azar found that obestatin was significantly higher in 73 obese children and adolescents . Although the obestatin serum concentration in obesity is controversial, its effect on food intake and obesity is not disputed.…”
Section: Discussionmentioning
confidence: 99%